Are lipid profiles, the concentration of calories, sodium and human milk water suitable to be offered to dehydrated neonate? (Research, Society and Development, 2020)
This study was conducted to analyze the lipid, caloric, sodium and water in colostrum, transitional milk and mature milk profile to assess whether the different phases of human milk are suitable to be offered to dehydrated term infant. A cross-sectional and quantitative design was chosen, using 44 human milk samples donated to the Human Milk Bank. As inclusion criteria, were selected samples of donors who exclusively breastfed. To evaluate the lipid profiles pools of the three phases were prepared, which were analyzed with the aid of electrospray ionization source mass spectrometry. Calorie, moisture and sodium analyzes were performed on individual samples using official AOAC methodologies. Lipid profiles indicated that pools may have important fatty acids that make up the triglycerides present in human milk lipids. The levels of sodium when evaluated individually varied significantly and in most samples were high when compared to the reference values. The average moisture content of mature milk was higher when compared to the other phases, which presented higher sodium content and lower moisture content (p